LESSON PLANNING IN YOUNG LEARNER:A DESCRIPTIVE STUDY TOWARDS TEACHERS' LESSON PLAN OF ELEMENTARY SCHOOL - Muhammad Dwi Wijayanto, - (2010)
ABSTRACT One of teachers' roles is as a lesson planner. Lesson plan plays an important role in teaching English especially as guidance for the teachers. This study was aimed at getting description of the aspects taken by teachers of elementary school in designing lesson plans. This study utilized qualitative research that applied descriptive study as its framework. The teachers of third to sixth grade in one elementary school in Bandung were involved in this study. There were 24 lesson plans gathered from four teachers. Based on the analysis using theories proposed by Reiser and Dick (1996) and Moon (2008) it can be concluded that generally the lesson plans analyzed are consistent with theories proposed by Reiser and Dick (1996) and Moon (2008) in terms of, for example, the teachers stated measurable objectives, presented information and examples, used media which were in line with young learner characteristic. However, the study also discovered inconsistency regarding some aspect of lesson plans. These include, for example, the teachers didn't state the goal, used immeasurable verb in objectives, were lack using real media.